The Palace of Nestor at Pylos in Western Messenia, Vol. II : The Frescoes - Lang, Mabel L. (Princeton, NJ : Princeton University Press, 2015)
From thousands of fragments of plaster the author has assembled clues to the scheme of the wall painting in this royal palace destroyed by fire at the end of the thirteenth century B.C.Originally published in 1969.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Foreword -- Contents -- The Palace of Nestor the Frescoes -- Catalogue -- Palace Survey of Plaster Remains and Decoration -- Outside Survey of Plaster Remains -- Conclusion -- Appendix -- Abbreviations and Bibliography -- Comparanda -- General Index -- Index of References to Illustrations -- Plates -- Plate Reference List
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: SOCIAL SCIENCE / Archaeology